2009
DOI: 10.3814/2009/789636
|View full text |Cite
|
Sign up to set email alerts
|

Differential Toxicological Interaction among Arsenic, Cadmium, Lead, and Mercury on MCF 7 Cell Line

Abstract: Evaluation of joint toxic action of metal ion mixtures is one of the priority research areas due to the simultaneous occurrence of metals in the environment and the health risk they posed to humans and the environment as a mixture. Individual and composite mixture acute toxicities of arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb), which are among the top eight toxic chemicals, were characterized at varying concentrations. MCF 7 cell lines were exposed to individual and composite mixtures containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…This study on mixture of metal ion can be used as a supporting data for metal induced toxicity by mixture of heavy metal ions using the AlOx bioassay. Recent reports on metal induced toxicological interactions using the MCF 7 cell line [ 25 ] and the enzyme urease [ 19 ] also support the additive nature of heavy metal ion mixtures, as reported in this work.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This study on mixture of metal ion can be used as a supporting data for metal induced toxicity by mixture of heavy metal ions using the AlOx bioassay. Recent reports on metal induced toxicological interactions using the MCF 7 cell line [ 25 ] and the enzyme urease [ 19 ] also support the additive nature of heavy metal ion mixtures, as reported in this work.…”
Section: Resultssupporting
confidence: 85%
“…The assay has been successfully extended for analysis of mixtures of Hg(II) along with Cd(II) and Pb(II). The inhibition patterns obtained are consistent with other reported studies using cell lines [ 25 ] and urease enzyme [ 19 ]. The developed method was applied to real samples such as drinking water and sea water samples with recoveries up to 110.52%.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…They found that cadmium modified the morphological characters on all cell lines at doses higher than 10 µM. Meanwhile, Klutse et al (2009) studied the toxicological interactions among metals on MCF-7 cell line. Cells were exposed to individual and composite mixture of the toxic metals according to their MCLs (maximum contamination levels) for 24 hours, cadmium was the second most toxic metal to the mammary cells and toxicity was enhanced three times higher in the composite mixture; healthy controlled subjects and concluded that mean cadmium concentration in cancer patients did not differ significantly from healthy control; although it was found in high concentrations in both groups.…”
Section: El-harouny Et Al mentioning
confidence: 99%
“…Aquatic environment is particularly susceptible to the accumulation of Cr, Cu and As during leachability from CCA treated wood, howbeit, there is dearth of information on the potential joint action toxicity of the metals in eliciting morbidity and mortality, growth retardation and induction of genetic instability in aquatic vertebrates. An increasing area of research focus in recent times, is the assessment of interactive effects among individual metals; which may lead to eliciting greater or lesser toxicity in biological systems via synergistic, antagonistic and/or additive interactive mechanisms [26][27][28]. The report herein is the first to utilize multi-model approach and cytogenetic biomarker to investigate the possible joint action toxicity of oxides of Cr, Cu and As on aquatic vertebrates using Clarias gariepinus as a model organism.…”
Section: Introductionmentioning
confidence: 99%